A contribution to Gymnosphaera (Cyatheaceae) in mainland Asia: Two new species, reinstatement of Cyathea bonii, and their phylogenetic positions. Issue 2 (13th October 2020) - Dong, Shi‐Yong; Zuo, Zheng‐Yu; Xiao, Yong; Huang, Ling; Pham, Van The; Phan, Ke Loc; Kang, Ming
Abstract: Gymnosphaera represents a minor lineage within the scaly tree‐fern family Cyatheaceae. Tropical and subtropical mainland Asia is a main distribution area of Gymnosphaera . However, the species diversity of Gymnosphaera is currently incompletely known in mainland Asia due to lacking critical revision. Here we present new findings of species diversity and their relationships to mainland Asian Gymnosphaera based on field surveys, the examination of herbarium collections, and phylogenetic analyses of sequences of multiple chloroplast and nuclear regions. Two new species, G. saxicola from southwestern Yunnan and G. bachmaensis from central Vietnam, are established. Traditionally recognized G. podophylla is revealed to be a complex, from which G. bonii is reinstated as a distinct species. Our phylogenetic analyses identified four clades within Gymnosphaera in mainland Asia: G. denticulata clade, G. gigantea clade, G. podophylla clade, and G. salletii clade. The new species G. saxicola, which is special for its saxicolous habitat, was resolved as sister to G. austroyunnanensis in the G. salletii clade. The newly discovered G. bachmaensis, which is characterized specially by the spathulate frond, was positioned in the G. podophylla clade, being sister to G. bonii . The mountainous region from south‐central Vietnam northwards to western Yunnan is a diverse center of Gymnosphaera and more species of this group are probably to be discovered there. Abstract : Phylogram of four species groups of Gymnosphaera from mainland Asia, each corresponding to a kind of sori arrangement. Positions of two new species ( G. saxicola and G. bachmaensis ) and the reinstated species ( G. bonii ) are designated with arrows in different colors.